(NuPRAWLENIE REVIMOM GORNYH LEDNIKOW I STOKOM REK (B/s - (NbAKALOW(B, (Nw(B.(Nd(B. s; (NgROMAN(B, (Nd(B.(Ns(B.s; (NpANOW(B, (Nw(B.(Nd(B.s; (NzALIHANOW(B, (NmIHAIL ~OKKAEWI^s; (NzALIHANOW(B, (NmIHAIL ~OKKAEWI^s ((NlENINGRAD (B:s (NgIDROMETEOIZDAT(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 228-237 (184 (NNAZW(B.)s
(NwYSOKOGORN(B. (NGEOFIZ(B. (NIN(B-(NTs
Keywords: (NlEDNIKI (B((NGEOL(B.) - (NrEVIMs; (NrEKI GORNYE (B- (NsTOK (B- (NuPRAWLENIEs